2018
DOI: 10.1098/rspb.2018.0372
|View full text |Cite
|
Sign up to set email alerts
|

Increased fluctuation in a butterfly metapopulation leads to diploid males and decline of a hyperparasitoid

Abstract: Climate change can increase spatial synchrony of population dynamics, leading to large-scale fluctuation that destabilizes communities. High trophic level species such as parasitoids are disproportionally affected because they depend on unstable resources. Most parasitoid wasps have complementary sex determination, producing sterile males when inbred, which can theoretically lead to population extinction via the diploid male vortex (DMV). We examined this process empirically using a hyperparasitoid population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…These values follow empirically observed ranges in a previously studied system (Nair et al, 2018). Temporally autocorrelated host abundance is generated by assuming a multiplicative effect of the noise…”
Section: The Individual-based Simulation Model Of a Spatially Strucsupporting
confidence: 80%
See 4 more Smart Citations
“…These values follow empirically observed ranges in a previously studied system (Nair et al, 2018). Temporally autocorrelated host abundance is generated by assuming a multiplicative effect of the noise…”
Section: The Individual-based Simulation Model Of a Spatially Strucsupporting
confidence: 80%
“…Modified from figure 3a in Zayed and Packer (2005) Adverse external factors (e.g., habitat loss, fragementation, pesticide application, climage change) boost parasitoid persistence. Two other studies examined particular systems with empirically parameterized models and likewise reported resilience of parasitoid populations (Nair et al, 2018;Weis et al, 2017). Nair et al (2018) reported that, although the proportion of DMs increased by threefold in the population of a parasitoid after the host populations crashed, their modeling results indicated little imminent risk of a diploid male vortex even if the host fluctuates with similar variability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations